Educational Pictures and Animation between Artistic Formation and Educational Reality - Bougaada, Karima; Mezhoud, Salim (Milev Journal of Research and Studies, 2021)
Through this research, we aim to learn about beauty centers in pictures and animation, and the role they play in shaping the aesthetic sense, and to achieve educational goals for the recipient, in order to address the problem of: To what extent do pictures and animation affect the development of the cognitive and aesthetic capabilities of the learner? We concluded from this research a number of results, the most important of which are: Pictures and educational animation affect the learner greatly because of their expressive and influential capacity, As the pictures and animation reflect the reality of the learner, providing him with an educational environment that suits his inclinations and stimulates his drive towards learning